STRENGTHENING THE ROLE OF INDIRECT TAXES IN STRENGTHENING THE REVENUE BASE OF BUDGETS OF ALL LEVELS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The problem of strengthening the relationship between taxpayers and the links of the state budget has been successfully addressed and the most important conditions and the effective functioning of budgets at all levels have been studied. Scientific recommendations for the effective redistribution of budget funds are given.